Patient characteristics and outcomes after ruxolitinib discontinuation in patients with myelofibrosis. (2nd July 2020) - Mascarenhas, John; Mehra, Maneesha; He, Jianming; Potluri, Ravi; Loefgren, Christina
Abstract: Background: This retrospective analysis evaluates morbidities, outcomes and associated risk factors in patients with myelofibrosis (MF) after ruxolitinib discontinuation, using Truven Health Analytics MarketScan (TR), Optum integrated virtual electronic health records and claims databases (OP), and Surveillance, Epidemiology, and End Results (SEER)-Medicare linked database (SM). Methods: A total of 290 patients with MF between 2006 and 2015 (using ICD-9 and ICD-O-3 codes), who were treated with and discontinued ruxolitinib were identified. Only patients with ≥90 days of medical history prior to index diagnosis (TR + OP) and Part A, B, and D enrollment at the time of index diagnosis (SM) were included. Morbidities were assessed during the 30-day period each following ruxolitinib initiation, prior to and post ruxolitinib discontinuation. Cumulative incidence of cytopenias and efficacy outcomes were evaluated from baseline. Results: Median age of patients was 68 years, with equal proportion of either gender. Median time to ruxolitinib discontinuation was 284 days and median follow-up after discontinuation was 70.9 days. The majority of patients were diagnosed with anemia and >30% of the patients received RBC transfusions during 30-day period prior to and the 30-day period post ruxolitinib discontinuation. After ruxolitinib discontinuation, half of the patients developed cytopenias. The median treatment progression-free survival, and overall survival after ruxolitinib discontinuation were 6.0 (4.4, 8.3) months and 11.1 (8.4, 14.5) months, respectively. Age at ruxolitinib discontinuation (HR [95% CI] = 2.071 [1.320, 3.248]), Charlson Comorbidity Index score (HR [95% CI] = 1.172 [1.093, 1.257]) and gender (HR [95% CI] = 1.620 [1.108, 2.369]) increased the risk of treatment progression (start of the subsequent treatment regimen) or death. Conclusion: Results from this large, retrospective, US population-based outcome analysis of MF patients show an increase in morbidity burden and identifies the risk factors of survival outcomes among real-world patients who have discontinued ruxolitinib.